Study of characteristics reliability of information transmission using a modified method of decoding - Зайцев, С. В. (Problems of Informatization and Control, 2013)
The article investigates the characteristics of reliability of information transmission in conditionsof jamming stations, electronic countermeasures, obtained by a statistical simulation,distributed programmable wireless systems using the proposed modified method of encodingand decoding of turbo codes and Walsh codes.